2016
DOI: 10.1121/1.4972530
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of linear and nonlinear ultrasound parameters with porosity and trabecular spacing in trabecular-bone-mimicking phantoms

Abstract: The speed of sound (SOS), the normalized broadband ultrasound attenuation (nBUA), and the nonlinear parameter (B/A) were measured in 18 trabecular-bone-mimicking phantoms consisting of water-saturated aluminum foams. The strong slow wave and the very weak fast wave were consistently observed in the signals transmitted through all of the phantoms. It was found that the SOS increased as the porosity and the trabecular spacing increased. In contrast, both the nBUA and the B/A showed opposite dependences on the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Correlation coefficients of B/A with apparent bone density (r = 0.95), BMD (r = 0.77), BV/TV (r = 0.80), and Tb.Th (r = 0.44) have been reported in bovine cancellous femur (0.5 MHz transmitter, 0.5 or 1 MHz receiver) [366][367][368]. Similar findings have been reported in aluminum-foam cancellous-bone-mimicking phantoms [328].…”
Section: F Nonlinear Properties Of Cancellous Bonesupporting
confidence: 78%
See 1 more Smart Citation
“…Correlation coefficients of B/A with apparent bone density (r = 0.95), BMD (r = 0.77), BV/TV (r = 0.80), and Tb.Th (r = 0.44) have been reported in bovine cancellous femur (0.5 MHz transmitter, 0.5 or 1 MHz receiver) [366][367][368]. Similar findings have been reported in aluminum-foam cancellous-bone-mimicking phantoms [328].…”
Section: F Nonlinear Properties Of Cancellous Bonesupporting
confidence: 78%
“…19) can exhibit slow wave phase velocity consistent with Biot theory [325][326][327]. A study on one set of aluminum foams indicates that SOS increases with porosity, but nBUA decreases with porosity [328]. Studies on nickel foams [329] and copper foams [330] indicate several properties that are consistent with cancellous bone: attenuation coefficient varies approximately as frequency to the first power [1], phase velocity exhibits negative dispersion [21,105,[148][149][150], and backscatter coefficient varies approximately as frequency cubed [274,275].…”
Section: Cancellous Bone-mimicking Phantomsmentioning
confidence: 57%
“…The opposite happens to the increasing trend of AIslow for parallel orientation versus porosity which due to the slow wave propagates through pore part of porous structure. When trabecular spacing and pore size growth, it boosts the flow of the fluid, which reduces the opposition of wave propagation, resulting in decreasing of the attenuation effect [24]. Previous research by Hosokawa et al [10], Kawasaki et al [5] and Otani [6] also reported the same outcome for the slow wave.…”
Section: Correlation Of the Wave Parameters With Various Porosities Amentioning
confidence: 70%
“…Thus, the selection of ROI, SOI and AR p-order should be carefully studied in vivo. Although BV/TV is one of the critical parameters to assess cancellous bones, previous studies have also reported the bone microstructures parameters, such as trabecular thickness, trabecular spacing, and porosity, have significant correlations with the ultrasonic backscatter parameters [64]- [67]. The correlations of these bone parameters with ultrasonic backscatter parameters were not addressed in this study and will be carried out in our future work.…”
Section: Limitationsmentioning
confidence: 81%